The process of transprofessional collaboration: how caregivers integrated the perspectives of rehabilitation through working with a physical therapist. Issue 4 (10th November 2020) - Goto, Ryohei; Haruta, Junji
Abstract : Objectives: To clarify the process of how caregivers in a nursing home integrate the perspectives of rehabilitation into their responsibilities through working with a physical therapist. Design: This study was conducted under an action research approach. Setting: The target facility was a nursing home located in Japan. The researcher, a physical therapist, worked at the nursing home once a week from April 2016 to March 2017. During the study period, he created field notes focused on the dialogue and action of caregivers regarding care, responses of caregivers to the physical therapist and reflections as a physical therapist. Caregivers were also given a short informal interview about their relationship with the nursing home residents. For data analysis, two researchers discussed the content based on the field notes, consolidating the findings. Participants: The participants were caregivers who worked at the target facility. Thirty-eight caregivers agreed to participate. Average age was 39.6±11.1 years, 14 (37%) were male and average caregiver experience was 9.8 years. Results: Two cycles of action research were conducted during the study period. There were four stages in the process of how caregivers in the nursing home integrated the perspectives of rehabilitation through their work with the physical therapist. First, caregivers resisted having the rehabilitation programme carried out in the unit because they perceived that rehabilitation performed by a physical therapist was a special process and not under their responsibility. However, the caregivers were given a shared perspective on rehabilitation by the physical therapist, which helped them to understand the meaning of care to adapt the residents' abilities to their daily life. They practised resident-centred care on a trial basis, although with a sense of conflict between their new and previous role, which emphasised the safety of residents' lives and personhood. The caregivers increased their self-efficacy as their knowledge and skills were supplemented by the physical therapist and his approval of their attempted care. They were then able to commit to their newly conceived specialty of care as a means of supporting the lives of residents. Conclusions: The process of working with a physical therapist led to a change in caregivers' perception and behaviours, which occurred in four stages: resistance to incorporation, recapture of other perspectives, conflicts and trials in the role of caregiver and transformation to a resident-centred perspective.